Identification and characterization of maize lines resistant to leaf diseases - Kaefer, Kaian Albino Corazza; Schuelter, Adilson Ricken; Schuster, Ivan; Marcolin, Jonatas; Vendruscolo, Eliane Cristina Gruszka (Semina: Ciências Agrárias, 2019)
Among the maize leaf diseases, white leaf spot, northern leaf blight, gray leaf spot, and southern rust are recognized not only by the potential for grain yield reduction but also by the widespread occurrence in the producing regions of Brazil and the world. The aim of this study was to characterize common maize lines for resistance to white leaf spot, northern leaf blight, gray leaf spot, and southern rust and suggest crosses based on the genetic diversity detected in SNP markers. The experiment was conducted in a randomized block design with three replications in order to characterize 72 maize lines. Genotypic values were predicted using the REML/BLUP procedure. These 72 lines were genotyped with SNP markers using the 650K platform (AffymetrixÂ®) for the assessment of the genetic diversity. Genetic diversity was quantified using the Tocher and UPGMA methods. The existence of genetic variability for disease resistance was detected among maize lines, which made possible to classify them into three large groups (I, II, and III). The maize lines CD 49 and CD50 showed a good performance and can be considered sources of resistance to diseases. Therefore, their use as gene donors in maize breeding programs is recommended. Considering the information of genetic distance together with high heritability for leaf diseases, backcrossing of parent genotypes with different resistance levels, such as those of the lines CD49 x CD69 and CD50 x CD16, may result in new gene combinations, as they are divergent and meet good performances.